2021
DOI: 10.1016/j.cjco.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Montreal-FH-SCORE Predicts Coronary Artery Calcium Score in Patients With Familial Hypercholesterolemia

Abstract: Background: Familial hypercholesterolemia (FH) is a monogenic disease characterized by a high concentration of low-density lipoprotein cholesterol. This population is considered to be at high cardiovascular risk; however, disease evolution remains heterogeneous among individuals. The coronary artery calcium (CAC) score is currently the best predictor of incidental major cardiovascular events in primary prevention in the general population. Few studies have described the CAC score in FH populations. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…In line with previous investigations [15,24,25], asymptomatic FH patients included in the present a cohort showed high prevalence and wide extension of CAD, reaffirming the notion that FH must be considered a high-risk group for premature atherosclerotic vascular damage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous investigations [15,24,25], asymptomatic FH patients included in the present a cohort showed high prevalence and wide extension of CAD, reaffirming the notion that FH must be considered a high-risk group for premature atherosclerotic vascular damage.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, AS doesn't take into account the presence of soft plaques, and even if several studies [24,25] suggested that it may be useful in ASCVD risk stratification, it cannot exclude reliably the presence of obstructive CAD. In this regard, in our population soft plaques were significantly more represented in the group with obstructive CAD and were the cause of complete vessel obstruction in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study of asymptomatic patients with FH, we found a significant number of zero calcium scores (45% of CCS, 48% of TCSasc, and 75% of TCSdsc). We found no similar studies on TCS in FH patients, but the CCS results are comparable to percentages reported by other authors [32]. However, interpreting TCSdsc results requires caution, as they may not adequately reflect the difference in the severity of atherosclerotic burden between both groups, owing to the high percentage of zero calcium scores.…”
Section: Limitations Of the Studysupporting
confidence: 58%
“…Furthermore, the MFHS can effectively identify patients who are currently receiving statin therapy but may require additional treatment to manage their cardiovascular risk. This can assist clinicians in identifying patients who require more intensive treatment 32,33 . The latest Canadian Cardiovascular Society Position Statement recommends the use of MFHS in the FH population 34 …”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%